Management of Demonstrations by Local Governments and Relevant Authorities: An Analysis of Their Roles and Impact on Public Order and the Protection of the Community - Annisa Pia (Asian Journal of Social and Humanities, 2026)
Demonstrations as a form of public participation in local democracy often face tensions with authorities, particularly when communication and conflict management mechanisms are ineffective. The demonstration at the Central Java Governor's Office in Semarang on August 29, 2025, which began peacefully but escalated into mass riots causing substantial damage and public disruption, highlights the urgent need to evaluate how local governments and relevant authorities manage demonstrations and their implications for public order and community protection. This research analyzes the role of local governments and relevant authorities in managing demonstrations, as well as their implications for public order and community protection. The study used a qualitative approach with narrative-descriptive analysis of interviews with 20 respondents (10 officers and 10 demonstrators) and linked them to a conflict governance lens. The data show that initially peaceful demonstrations turned into mass riots due to the motive of demands for justice for victims of violence by officers and rejection of government policies deemed not in favor of the people. The security approach of officers was predominantly repressive, while the Public Order Agency (Satpol PP) played an administrative role. There was a sharp contrast in perception between officers who considered security measures in accordance with SOPs and demonstrators who considered the actions arrogant and traumatic. Conflict governance is still oriented solely towards maintaining order, thus recommending a transformation to a dialogue policing model, the implementation of the Elaborated Social Identity Model, multi-agency coordination, digital narrative monitoring, and human rights-based post-action evaluation.